EVALUASI KESESUAIAN LAHAN TANAMAN TOMAT DI NAGARI AIA DINGIN KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK (Universitas PGRI Sumatera Barat, 2011)
This study aims to evaluate land suitability of tomato plants and createmaps of land suitability of tomato plants in the Valley of the Nagari Aia ColdGumanti Solok District. Soil at the sites is soil that develops Andisol of volcanicrocks. The unit of analysis in this study is the suitability of tomato crop land inNagari Aia Cold Valley Gumanti Solok District. Corresponding map of thelocation of the study Nagari cold Aia Valley Gumanti Solok District 1: 50,000scale in order to get the five points that the samples Jorong Data, Jorong Koto,Jorong Aia Sonsang (dryland) and Jorong Aia Sonsang and Jorong Data (wetland/ paddy). The data analysis conducted in the field and in the laboratory by meansof